2014
DOI: 10.1002/jssc.201400290
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation workflow for the liquid chromatography tandem mass spectrometry based analysis of nicotinamide adenine dinucleotide phosphate cofactors in yeast

Abstract: The accurate quantification of the highly unstable intracellular cofactor nicotinamide adenine dinucleotide phosphate in its oxidized and reduced forms demands a thorough evaluation of the analytical workflow and dedicated methods reflecting their solution chemistry as well as the biological importance of their ratio. In this work, we present a workflow for the analysis of intracellular levels of oxidized and reduced nicotinamide adenine dinucleotide phosphate in the yeast Pichia pastoris, including hot aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The reason for the high ratios was probably the oxidation of NADH and NADPH and, consequently, an increased concentration of NAD + and NADP + [32,33]. However, Hou and coworkers [39] reported data for the NAD + /NADH and NADP + /NADPH ratios that were close to those measured in the current study.…”
Section: Application Of the Methodssupporting
confidence: 50%
See 1 more Smart Citation
“…The reason for the high ratios was probably the oxidation of NADH and NADPH and, consequently, an increased concentration of NAD + and NADP + [32,33]. However, Hou and coworkers [39] reported data for the NAD + /NADH and NADP + /NADPH ratios that were close to those measured in the current study.…”
Section: Application Of the Methodssupporting
confidence: 50%
“…In the case of NADPH, only one peak for NADP + was observed. As previously reported in the literature [32], ammonium acetate (pH 8.0) has been shown to improve the stability of NADPH and reduce the oxidation. To investigate this, the standards of NADH and NADPH were prepared in 5 mM ammonium acetate (pH 8.0), which indeed reduced the oxidation of these two compounds.…”
Section: Evaluation Of Oxidation Of Nadh and Nadph To Nad + And Nadp mentioning
confidence: 80%
“…Ortmayr, et al , conducted an extensive stability and analysis validation on NAD(H)/NADP(H) and reported that NADH and NADPH have a relatively short half-life at a pH lower than 6, and NADPH was only stable at pH 8. 9 Therefore, for analysis of a large number of samples, buffering samples with 5 mM ammonium acetate at pH 8 may be desirable as the highly liable NADPH was stable for at least 24 hours under these conditions. LC-MS based analysis of NAD metabolites may also present some unique and unexpected challenges that analysts should be aware of.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study by Ortmayr, et al specifically noted the lack of available stable isotope labeled analogs as an impediment to conducting rigorous and reproducible NAD metabolite analysis. 9 Furthermore, since LC-high resolution MS (LC-HRMS) also permits simultaneous metabolite quantitation and tracing with isotope-specific resolution, a diversity of stable isotope labels ( e.g. 2 H, 13 C, and/or 15 N) can be introduced by experimental design and distinguished by the HRMS.…”
Section: Introductionmentioning
confidence: 99%
“…Our research shows that long-term nicotinamide overload can cause insulin resistance and oxidative stress, and eventually lead to diabetes [3,4] . Currently, the detection of nicotinamide in plasma samples is a complex method, which requires high instrument conditions and liquid chromatography -mass spectrometry [5][6][7] . This method is also highly timeconsuming, mainly due to the very low levels of nicotinamide in the plasma.…”
mentioning
confidence: 99%